PLURALISM IN THE PERSPECTIVE OF KH ABDURRAHMAN WAHID: AN INTRODUCTION TO MULTICULTURAL EDUCATION - Nur‘Aini, Khoirun Nisa; Nurhuda, Abid; Huda, Ali Anhar Syi’bul (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
Indonesia is a country that is rich in diversity so one of the leading thinkers of democracy and pluralism emerged, namely KH. Abdurrahman Wahid was born in Jombang, East Java, and is usually called Gus Dur. He is a reform thinker in this field and even instilled the concept of indigenous Islam in Indonesia so he is called the Father of Pluralism in the World. So the purpose of this study is to describe pluralism from the perspective of KH Abdurrahman Wahid. This research method is a literature study with a socio-historical and factual historical approach to reveal real past events. The results of the study show that Pluralism in KH Abdurrahman Wahid's Perspective is the view that every religion has differences, characteristics, and uniqueness of each, and not equate all religions to foster a spirit of tolerance among human beings to create peace in life.